Magnetism of a very young lunar glass. Issue 10 (30th October 2015) - Buz, Jennifer; Weiss, Benjamin P.; Tikoo, Sonia M.; Shuster, David L.; Gattacceca, Jérôme; Grove, Timothy L.
Abstract: Recent paleomagnetic studies of Apollo samples have established that a core dynamo existed on the Moon from at least 4.2 to 3.56 billion years (Ga). Because there is no lunar dynamo today, a longstanding mystery has been the origin of magnetization in very young lunar samples (<~200 million years old (Ma)). Possible sources of this magnetization include transient fields generated by meteoroid impacts, remanent fields from nearby rocks magnetized during an earlier dynamo epoch, a weak late dynamo, and spontaneous remanence formed in a near‐zero field. To further understand the source of the magnetization in young lunar samples, we conducted paleomagnetic, petrographic, and 40 Ar/ 39 Ar geochronometry analyses on a young impact melt glass rind from the exterior of ~3.35 Ga mare basalt 12017. Cosmic ray track densities and our 40 Ar/ 39 Ar and cosmogenic 38 Ar analyses constrain the glass formation age to be <7 Ma and most likely <20 thousand years (kyr), making it likely the youngest extraterrestrial sample yet studied with paleomagnetic methods. Despite its relatively high fidelity magnetic recording properties compared to most lunar rocks, we find that the glass carries no stable primary natural remanent magnetization and that it formed in a field <~7 μT (with a 2  σ upper limit of <11 μT). Given the poor magnetic recording properties of the majority of lunar samples, this provides further evidence that many or perhaps even all previous paleointensity estimates for ≤1.5 Ga rocks are upper limits on the true paleofield and therefore require neither a protracted strong (>10 μT) core dynamo field nor impact‐generated fields. Key Points: Apollo basalt 12017 has a glass rind with an age <7 Ma old The 12017 glass has little or no stable natural remanent magnetization There is no robust paleomagnetic evidence for a lunar dynamo after ~3.56 Ga